Hakikat Keuangan Perseroan Terbatas Pada Bumn Di Indonesia - Akhdharisa, Muhammad (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
The purpose of this study is to know and explain the nature financial of limited liability company finances in State-Owned Enterprises in Indonesia, the system management accountability financial of state-owned limited liability company in Indonesia, the financial legal position of limited liability company in state owned enterprises in Indonesia. This type of research is descriptive analytical with the type of normative legal research. The approach used is the doctrinal approach or also known as the normative approach, which studies and analyzes the rules, standards and legal principles of the nature of corporate finance in state-owned enterprises in the form of limited liability companies. Source of data collected include primary, secondary and tertiary data. Data analysis in normative legal research, data processing is carried out by means of a systematic method of written legal materials. Systematization means making a classification of these legal materials to facilitate analysis work. The result of this study indicated that the nature of limited liability company finance in Indonesia is the company’s finance itself as a legal entity that as separate assets from iths shareholders so that it cannot be called state finance, the state-owned limited liability company financial accountability management system in Indonesia shows that companies with limited liability, not only the ownership of assets by the company, are separate from the money owned by the people who run the company but also the company’s shareholders are not responsible for the company’s debt, and the financial legal position of a state-owned enterprises limited liability company in Indonesia is interpreted as being a shareholder like a shareholder in a limited liability company.